Nucleoside Antiviral Therapy for Herpes Zoster: A Literature Review - Ain, Nisrina Huurul; Rahmatullah, Lalu Mas’ud; Utari, Widi Gustita; Nuralyza, Imasayu; Salsabiella, Baiq Rani; Maghfirahandini, Reivirly Khairadaty; Aini, Siti Rahmatul; Nurhidayati, Nurhidayati (Jurnal Biologi Tropis, 2025)
Herpes zoster is a viral skin infection caused by the reactivation of the varicella-zoster virus, which remains latent in the dorsal root ganglia of the spinal cord and the cranial sensory ganglia. One of the most widely used classes of antiviral agents in the treatment of herpes zoster is nucleoside analogs. This study aims to review the use of nucleoside analogs in the management of herpes zoster. The method employed was a literature review of relevant research articles. The findings indicate that nucleoside analogs commonly used in herpes zoster therapy include acyclovir, valacyclovir, famciclovir, and brivudine. These agents are administered in various doses, routes, and therapeutic purposes, such as alleviating acute symptoms, accelerating skin lesion healing, preventing postherpetic neuralgia, and serving as prophylactic therapy in special conditions such as cancer or organ transplantation. Overall, the use of nucleoside analogs has proven effective in inhibiting varicella-zoster virus replication, reducing symptom intensity, and minimizing the risk of complications.